2007
DOI: 10.1037/0090-5550.52.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden in Huntington's disease.

Abstract: Objective: Huntington's disease (HD) is an autosomal dominant heritable disease characterized by progressive neuron death and subsequent degeneration of motor, cognitive, and emotional functioning. Caregiver research studies in HD are few. The purpose of the current study was to examine caregiver burden in HD. Method: The sample consisted of 62 pairs of caregivers and care receivers (persons with Huntington's disease; pHDs). Caregivers were assessed regarding their psychological functioning, subjective apprais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 31 publications
4
39
0
1
Order By: Relevance
“…These findings suggest that caregivers who are more satisfied have a lower probability to perceive high burden and to be thus exposed to burnout risk. These results were in line with studies conducted with caregivers of people with different diseases (Bassi et al, 2014;Brouwer, Exel, Berg, Bos, & Koopmanschap, 2008;Cohen, Colantonio, & Vernich, 2002;Pickett, Altmaier, & Paulsen, 2007). Moreover, the recent mental health continuum model (Keyes, 2007) provided empirical support to the WHO's definition of health as presence of well-being, showing that wellbeing and ill-being dimensions belong to two different and relatively independent continua, rather than being opposite poles of the same continuum.…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggest that caregivers who are more satisfied have a lower probability to perceive high burden and to be thus exposed to burnout risk. These results were in line with studies conducted with caregivers of people with different diseases (Bassi et al, 2014;Brouwer, Exel, Berg, Bos, & Koopmanschap, 2008;Cohen, Colantonio, & Vernich, 2002;Pickett, Altmaier, & Paulsen, 2007). Moreover, the recent mental health continuum model (Keyes, 2007) provided empirical support to the WHO's definition of health as presence of well-being, showing that wellbeing and ill-being dimensions belong to two different and relatively independent continua, rather than being opposite poles of the same continuum.…”
Section: Discussionsupporting
confidence: 88%
“…The psychiatric burden of knowing a loved one is suffering from a life-limiting illness is stressful for caregivers, with caregivers having up to a 60% increase in mortality compared to non-caregivers 21. In neurodegenerative conditions, caregiver quality of life, burnout, and clinically significant depression are highly correlated with the severity of patient physical disability and neuropsychiatric symptoms 22,23…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…Moreover, caregiver burden in HD is positively and strongly associated with the affected individual's level of depression (Pickett Jr., Altmaier, & Paulsen, 2007)-an issue that research has shown can be ameliorated via social problem-solving therapy when SPS is deficient. In fact, psychiatric and behavioral issues-likely captured by this research and the inclusion of the novel SPS instrument-are the most frequently cited reasons for individuals with HD being institutionalized by caregivers (Rosenblatt & Leroi, 2000;van Duijn et al, 2007).…”
Section: Social Problem-solvingmentioning
confidence: 99%